2020
DOI: 10.1101/2020.01.20.20017723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequent Daytime Napping is Detrimental to Human Health: A phenotype-wide Mendelian Randomization Study

Abstract: Background: It remains controversial whether daytime napping is beneficial for human health. Objective: To examine the causal relationship between daytime napping and the risk for various human diseases. Design: Phenotype-wide Mendelian randomization study. Setting Non-UK Biobank cohorts reported in published genome-wide association studies (GWAS) provided the outcome phenotypes in the discovery stage. The UK Biobank cohort provided the outcome phenotypes in the validation stage. Participants: The UK Biobank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…First, the causal pathway from napping to obesity and then to diabetes could not be confirmed in this study. However, previous prospective cohort studies and Mendelian 24] and obesity [21][22][23][24]27]. These results support the causal link being inferred.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…First, the causal pathway from napping to obesity and then to diabetes could not be confirmed in this study. However, previous prospective cohort studies and Mendelian 24] and obesity [21][22][23][24]27]. These results support the causal link being inferred.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, reverse causation (i.e., patients with diabetes tended to have daytime napping) cannot be ruled out, although daytime napping is a long-accepted culture in China, which might have been formed since young age. Notably, previous prospective cohort studies and Mendelian randomization have shown a positive association from daytime napping to obesity, but not vice versa [21][22][23][24], supporting the causal direction from napping to obesity. Second, assessment of daytime napping was self-reported and thus misclassification error was possible.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation